An Appalachian isochron: a kaolinized carboniferous air-fall volcanic-ash deposit (tonstein) - Lyons, Paul C.; Outerbridge, William F.; Triplehorn, D. M.; Evans, Howard D., jr.; Congdon, Roger D.; Capiro, Mirtha; Hess, Jürgen C.; Nash, William P. (The Geological Society of America bulletin, 1992)
The Fire Clay tonstein is a kaolinized, airfall volcanic ash bed that was deposited in a widespread late Carboniferous peat-forming mire. Eleven samples from Kentucky and West Virginia, spanning a distance of 200 km, and two samples from Tennessee and Virginia indicate a characteristic mineralogical signature, as compared with other Appalachian tonsteins, consisting of well-crystallized kaolinite, beta-quartz crystal paramorphs, sanidine, ilmenite, zircon, and brookite. Detrital illite and quartz are rarely present or are in very small amounts, which indicates rapid deposition in a mire. Several normal graded cycles in this tonstein suggest repeated episodes of pyroclastic activity that produced a composite ash layer.A high-silica alkalic rhyolitic source is suggested by the geochemistry of immobile elements and by electron-probe analyses of glass inclusions in volcanic quartz from the Fire Clay tonstein. The rare-earth-element plots (chondrite normalized) of the tonstein show a pronounced negative Eu anomaly and relatively high concentrations of Zr and Th, which are both indicative of a rhyolitic source. Probe analyses of the Fire Clay glass inclusions from four states indicate a chemically identical high-silica rhyolite with peraluminous affinities.40Ar/39Ar sanidine plateau dating indicates an age of 312 ± 1 Ma for the Fire Clay tonstein, which is consistent with previous 40Ar/39Ar dates for this tonstein. This age is in agreement with a late Westphalian B age in the European Carboniferous chronostratigraphy on the basis of an age of 311 Ma for the Westphalian B/C boundary.A new isopachous map of the Fire Clay ash-fall deposit indicates an area of 37,000 km2 and a probable source to the present-day southwest. The deposit has a minimum preserved compacted volume of 2.8 km3, which corresponds to an original uncompacted volume of about 20 km3. This preserved volume indicates an ultraplinian volcanic explosion. Pindell and Dewey (1982) proposed an Andean-type arc in this block during the late Carboniferous, prior to South American-North American plate collision. We hypothesize an associated back-arc caldera system in the Yucatan block to explain the high-silica, potassic rhyolitic ash that gave rise to the Fire Clay tonstein.